Cerebral Hemodynamics in Moyamoya Disease: Correlation between Perfusion-Weighted MR Imaging and Cerebral Angiography - Togao, O.; Mihara, F.; Yoshiura, T.; Tanaka, A.; Noguchi, T.; Kuwabara, Y.; Kaneko, K.; Matsushima, T.; Honda, H. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: In Moyamoya disease, the relationship between cerebral hemodynamics and angiographic findings has not been fully evaluated. The purpose of this study is to evaluate hemodynamics in Moyamoya disease with perfusion-weighted MR imaging (PWI) and cerebral angiography.METHODS: Twenty patients with Moyamoya disease were the subjects. Mean transit time (MTT) derived from PWI was calculated in the medial frontal lobes, the posterior frontal lobes, the occipital lobes, and the basal ganglia. From the angiographies, we classified the degrees of internal carotid artery (ICA) and posterior cerebral artery (PCA) stenoses as well as the degrees of Moyamoya vessels and leptomeningeal anastomosis (LMA). MTT in each region was compared with the angiographic findings.RESULTS: MTT positively correlated with the degree of ICA stenosis in the medial frontal (P < .01), posterior frontal (P < .001), and occipital (P < .001) lobes, as well as in the basal ganglia (P < .001). MTT correlated with the degree of PCA stenosis in the medial frontal (P < .001), posterior frontal (P < .001), and occipital (P < .001) lobes, as well as in the basal ganglia (P < .001). MTT correlated with the degree of Moyamoya vessels in the medial frontal (P < .05) and posterior frontal (P < .01) lobes. A multivariate analysis revealed that ICA and PCA stenoses and Moyamoya vessels were independent factors that prolonged MTT.CONCLUSION: Both ICA and PCA stenoses may influence overall cerebral perfusion in Moyamoya disease. The development of Moyamoya vessels may indicate hemodynamic impairment.